Access to sources of stable, sustainable, and modern energy as a goal of sustainable development in the European Union: Are the Scandinavian countries leading the energy transition? - Krzysztof Adam Firlej; Chrystian Firlej; Lidia Luty (Entrepreneurial Business and Economics Review (EBER), 2024)
Objective: The objective of the article is to classify European Union (EU) member states according to similarity in the area of sustainable development goal 7 (SDG7) of the United Nations (UN) Agenda 2030 on affordable and clean energy. Research Design & Methods: We conducted a hierarchy of EU countries using the linear ordering method due to the level of achievement of sustainable development goal 7 based on indexes available in the Eurostat database for the years 2015 and 2021. We preceded the selection of the method for ordering objects by applying several procedures (Hellwig method (HELLWIG); Technique for order of preference by similarity to ideal solution (TOPSIS); standardized value Sums method (SSW); zeroed unitarization method (IUCN) proposed in the literature. Next, we used a procedure to support the selection of the method based on the measure of inter-ranking comparisons. Moreover, we singled out high-performing countries and countries that require increased attention and support to facilitate the transition to a greener energy economy. Findings: The article presents the ranking of countries by level of achievement of SDG 7 in 2021 and 2015 using the IUCN method. The hypotheses that proclaim the Scandinavian countries (Sweden and Denmark) as leaders in the implementation of SDG7 in the European Union and forming the cluster with the highest degree of SDG7 implementation were verified positively. The results obtained for each group of countries indicate strong development disparities among member countries in the area of clean and accessible energy in its various aspects. Implications & Recommendations: The econometric optics proposed in the study and its results can help classify EU member states in terms of achieving SDG7 for researchers and policymakers. Scholars may supplement the proposed research approach with further measures of clean and accessible energy beyond the SDG7 monitoring indexes. Such indexes could include energy prices, which affect the scale of energy poverty, or the level of greenhouse gas emissions on which environmental well-being depends, among others. Contribution & Value Added: The study narrowed the knowledge gap on the choice of the linear ordering method for objects, often used in socio-economic research. The use of an original research approach different from previous work for the new timeframe supports filling the research gap in empirical studies concerning the classification of European Union member states in terms of SDG7 implementation.
Keywords: O13; P18; Q42; 330; sustainable development; clean energy; accessible energy; SDG 7; EU countries; classifi-cation; typology; sustainable development goal; sustainable energy management